Pengaruh Green Product Knowledge, Lifestyle, Hedonic Shopping Motivation, Environmental Awareness Terhadap Brand Loyalty (Studi Kasus pada Pengguna The Body Shop di Kota Malang) - Amanda, Dita; Rizal, Mohammad; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine whether the influence of green product knowledge, lifestyle, hedonic shopping motivation and environmental awareness on brand loyalty in users of The Body Shop in Malang City. This type of research is explanatory research using a quantitative approach. The population in this study were users of The Body Shop in Malang City who had purchased The Body Shop products. The sample used was 95 respondents. The data collection technique used a questionnaire. Data analysis using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, F test (simultaneous), t test (partial), and the coefficient of determination (adjusted R2), through SPSS 25 tools. The results showed that the green product knowledge variable partially influenced brand loyalty. Lifestyle variables partially affect brand loyalty. Hedonic shopping motivation variable partially affects brand loyalty. The enviromental awareness variable partially affects brand loyalty. Green product knowledge, lifestyle, hedonic shopping motivation and enviromental awareness variables simultaneously affect brand loyalty.  Keywords: Green Product Knowledge, Lifestyle, Hedonic Shopping Motivation, Environmental Awareness, Brand Loyalty